Nitration of N-acetyl anilides using silver(I) nitrate/persulfate combination - Sanjeam H. (2023)
Nitration of N-acetyl anilides using a simple combination of AgNO3 and K2S2O8 as a stable nitro source and an oxidant, respectively, was explored. The reaction was practical to operate and proceeded under considerably mild reaction conditions (reflux in acetonitrile) within acceptable reaction time (6 h). The para-substituted N-acetyl anilides gave only ortho-nitrated products in moderate to good yields (30–63% yields). The ortho-, meta-, or non-substituted N-acetyl anilides gave a mixture of nitrated products (30–72% combined yields) with preferentially at the para- over the ortho-position (ortho:para; 1.0:1.1–1.0:2.8).